A common ground switched-quasi-Z-source bidirectional DC-DC converter with wide-voltage-gain range for EVs with hybrid energy sources - Zhang, Yun; Liu, Qiangqiang; Li, Jing; Sumner, Mark (Institute of Electrical and Electronics Engineers, 2018)
A common ground switched-quasi-Z-source bidirectional DC-DC converter is proposed for electric vehicles (EVs) with hybrid energy sources. The proposed converter is based on the traditional two-level quasi-Z-source bidirectional DC-DC converter, changing the position of the main power switch. It has the advantages of a wide voltage gain range, a lower voltage stress across the power switches, and an absolute common ground. The operating principle, the voltage and current stresses on the power switches, the comparisons with the other converters, the small signal analysis and the controller design are presented in this paper. Finally, a 300W prototype with Uhigh=240V and Ulow=40~120V is developed, and the experimental results validate the performance and the feasibility of the proposed converter.